Women Specific Characteristics and 1-Year Outcome Among Patients Hospitalized for Peripheral Artery Disease: A Monocentric Cohort Analysis in a Tertiary Center - Détriché, Grégoire; Guédon, Alexis; Mohamedi, Nassim; Sellami, Olfa; Cheng, Charles; Galloula, Alexandre; Goudot, Guillaume; Khider, Lina; Mortelette, Hélène; Sitruk, Jonas; Gendron, Nicolas; Sapoval, Marc; et al. (Frontiers in Cardiovascular Medicine, 2022)
Although women have lower age-standardized cardiovascular disease incidence, prevalence, and death-related rates than men, there are also reports indicating that women with cardiovascular disease receive less care, fewer investigations, and have poorer outcomes after a coronary event. The aims of this study were to compare the characteristics of men and women hospitalized for lower extremity arterial disease (LEAD), their cardiovascular and limb outcomes, and their one-year mortality. The study is a prospective registry collecting data about all consecutive patients hospitalized for LEAD within the vascular department of the Georges-Pompidou European Hospital (Paris, France). Patients were required to have one of three inclusion criteria: previous revascularization of the lower limb or any lower limb artery occlusion due to an atherosclerotic vascular disease or hemodynamic evidence of LEAD. Exclusion criteria were patients with lower extremity arterial occlusion due to another cause. All patients were followed-up for at least 12 months after the initial hospitalization. Among the 235 patients included, women (26 %) were older than men with a median age of 75.6 and 68.3 years respectively. Main cardiovascular risk factors and comorbidities were similar for men and women except more former or current smokers (83.4 vs. 54.1%) and more history of coronary heart disease (24.1 vs. 11.5%) in men. Most patients (58.8%) had critical limb ischemia and 41.3% had claudication, with no difference for sex. After discharge, patients received an antithrombotic therapy for 93.2%, a lipid-lowering drug for 86.9%, an angiotensin converting enzyme inhibitor or angiotensin-receptor blocker for 78.9%, similarly between sex. At one-year, overall survival, major adverse cardiovascular events, major adverse limb events did not differ with 13.2%, 6.3% and 18.4% in men, and 13.1%, 4.9%, 24.6% in women, respectively, despite the difference in age. Overall mortality, cardiovascular outcomes, limb revascularization or amputation did not differ between men and women, one year after hospitalization for LEAD although the latter were older, less smoker and had less coronary artery disease. Future research is needed to better understand sex-specific mechanisms in the pathophysiology and natural history of LEAD.